2019
DOI: 10.3390/cancers11050673
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 Contributes to the Resistance of Melanoma Cells to the Multikinase Inhibitor Dasatinib

Abstract: Malignant melanoma is the most aggressive skin cancer and can only be cured if detected early. Unfortunately, later stages of the disease do not guarantee success due to the rapid rate of melanoma cell metastasis and their high resistance to applied therapies. The search for new molecular targets and targeted therapy may represent the future in the development of effective methods for combating this cancer. SIRT2 is a promising target; thus, we downregulated SIRT2 expression in melanoma cells in vertical growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 94 publications
(118 reference statements)
2
35
1
Order By: Relevance
“…Karwaciak and colleagues [ 68 ] demonstrated that the SIRT2 inhibitor AC-93253 inhibits the expression of genes involved in the progression and chemoresistance of melanoma, influencing proliferation and apoptosis. They also demonstrated that SIRT2 inhibition makes melanoma cells sensible to dasatinib [ 69 ]. Furthermore, SIRT1&2 knockdown inhibits proliferation and decreases colony formation in melanoma cells [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Karwaciak and colleagues [ 68 ] demonstrated that the SIRT2 inhibitor AC-93253 inhibits the expression of genes involved in the progression and chemoresistance of melanoma, influencing proliferation and apoptosis. They also demonstrated that SIRT2 inhibition makes melanoma cells sensible to dasatinib [ 69 ]. Furthermore, SIRT1&2 knockdown inhibits proliferation and decreases colony formation in melanoma cells [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, for the first time, we have demonstrated that SIRT2 could contribute to cisplatin sensitivity. Previously, SIRT2 was reported to increase the resistance of anticancer drugs in melanoma and nasopharyngeal carcinoma [ 27 , 41 ]. These results seem contradictory but also make great sense in view of the dual tumor suppressive and oncogenic role of SIRT2 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As an example for the latter, inhibition of SIRT1 by the up-regulation of miR-211-5p was associated with the induction of apoptosis in breast cancer cells (91). Inhibition of SIRT2 has been confirmed to induce the susceptibility of melanoma cell to the multikinase inhibitor dasatinib (92).…”
Section: Special Aspects Of Novel Epigenetic and Metabolic Therapeutimentioning
confidence: 93%